2012
DOI: 10.1039/c2ob25089f
|View full text |Cite
|
Sign up to set email alerts
|

Hypervalent iodine mediated synthesis of carbamate protected p-quinone monoimine ketals and p-benzoquinone monoketals

Abstract: A simple and efficient method for the synthesis of p-quinone monoimide ketals and p-benzoquinone monoketals by using a hypervalent iodine reagent, diacetoxyiodobenzene, has been developed. These two types of ketals are achieved from a single starting material by varying the reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Quinones and quinone ketals, as well as cyclohexadienones, have long served as useful synthetic intermediates to construct densely functionalized aromatic rings and cyclohexanes . Accordingly, their application in asymmetric catalysis, especially organocatalysis, has been on the rise as an expedient means to deliver a range of optically enriched molecules. , On the other hand, their nitrogen analogs, quinone imines and quinone imine ketals have rarely been utilized in asymmetric catalysis, despite their ready accessibility from the corresponding aniline derivatives and wide use in natural product synthesis. To the best of our knowledge, use of N-sulfonyl quinone imines in enamine catalysis as a way to perform α-arylation of aldehydes is the only example reported to date, and quinone imine ketals have never been applied in asymmetric catalysis. Moreover, regardless of the general fact that these imines can be electrophilically activated by a catalytic amount of an acid, , chiral acid catalyzed asymmetric transformations have yet to be developed.…”
mentioning
confidence: 99%
“…Quinones and quinone ketals, as well as cyclohexadienones, have long served as useful synthetic intermediates to construct densely functionalized aromatic rings and cyclohexanes . Accordingly, their application in asymmetric catalysis, especially organocatalysis, has been on the rise as an expedient means to deliver a range of optically enriched molecules. , On the other hand, their nitrogen analogs, quinone imines and quinone imine ketals have rarely been utilized in asymmetric catalysis, despite their ready accessibility from the corresponding aniline derivatives and wide use in natural product synthesis. To the best of our knowledge, use of N-sulfonyl quinone imines in enamine catalysis as a way to perform α-arylation of aldehydes is the only example reported to date, and quinone imine ketals have never been applied in asymmetric catalysis. Moreover, regardless of the general fact that these imines can be electrophilically activated by a catalytic amount of an acid, , chiral acid catalyzed asymmetric transformations have yet to be developed.…”
mentioning
confidence: 99%
“…We initiated our studies by converting protected aniline to the corresponding imine-ketal 24 core following the reaction with α-bis(boryl)carbanions, but no desired product formation occurs. Further optimization revealed that the isolation in quinketal 25 , 26 stage is necessary for good yield. A good number of anilines were converted to the corresponding aldehydes and ketones in good yields (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…General Information : All reagents and deuterated solvents were commercially available and used without further purification. The sufonyl hydrazides 1 a – 1 d , N ‐substituted maleimides [15a] 2 a – 2 f , para ‐quinone methides ( p ‐QMs) [15b] 2 g – 2 j and quinone imine ketal [15c] 2 l are known compounds and were prepared according to previously described procedures. All experiments were carried out in oven‐dried round‐bottom flask equipped with a stirring bar.…”
Section: Methodsmentioning
confidence: 99%